2004
DOI: 10.1111/j.1475-097x.2004.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular long‐axis function in relation to left ventricular systolic function

Abstract: A decrease in left ventricular (LV) systolic function is accompanied by a decrease in maximal relaxation velocity in LV long-axis direction, but is it also accompanied by a decrease in right ventricular (RV) long-axis function? To study this 35 consecutive patients were examined by echocardiography. Ejection fraction (LVEF) and mitral annulus motion (MAM) were used as indices of LV systolic function and tricuspid annulus motion (TAM), that is the systolic shortening in RV long-axis direction, was used as an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Furthermore, mitral annular movement contributes to LA filling by creating a suction effect during systole and it contributes to LA emptying by decreasing LA volume during diastole. [12][13][14] In our study, the LAAEV pre-PBMV was lower than normal, and we found a significant increase in LAAEV post-PBMV. Similar to our study, Tatani S.B et al 16 found a significant improvement of the left appendicular flow after PBMV.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Furthermore, mitral annular movement contributes to LA filling by creating a suction effect during systole and it contributes to LA emptying by decreasing LA volume during diastole. [12][13][14] In our study, the LAAEV pre-PBMV was lower than normal, and we found a significant increase in LAAEV post-PBMV. Similar to our study, Tatani S.B et al 16 found a significant improvement of the left appendicular flow after PBMV.…”
Section: Discussionsupporting
confidence: 45%
“…Mitral annulus has an important role for LA and left ventricular (LV) function by moving throughout LV long axis. [12][13][14] In patients with MS, LV, LA, and LAA functions are impaired and the excursion of mitral annulus is reduced due to scarring and inflammatory processes. 15 The LV long-axis function which is a useful echocardiographic index of LV systolic function can be evaluated by measuring Sawave velocity obtained by TDI.…”
Section: Discussionmentioning
confidence: 99%
“…Although Fabry disease‐related infiltrative hypertrophic cardiomyopathy has been clearly described in terms of LV involvement 4,7–10, to date RV findings have not been examined in detail. This study has shown that RV involvement is common and affects more than one‐third of all patients with Fabry disease.…”
Section: Discussionmentioning
confidence: 99%
“…, 2002) at the lateral site. The maximal relaxation velocity of the tricuspid annulus was measured in the same way (Emilsson, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…The maximal relaxation velocity of the mitral annulus was measured as the steepest part of the curve in early diastole (Nilsson et al, 2002) at the lateral site. The maximal relaxation velocity of the tricuspid annulus was measured in the same way (Emilsson, 2004).…”
Section: Echocardiographic Examinationmentioning
confidence: 99%